Interrogating the Relationship Between Bargaining Structures and Bargaining Outcomes for Contract Academic Faculty in Ontario - Ross, Stephanie; Savage, Larry; Watson, James (Labour / Le Travail, 2020)
This article uses case studies from three comparable Ontario-based universities to explore the relationship between bargaining unit structures and collective bargaining outcomes for unionized sessional contract academic faculty. The article charts the complex network of bargaining unit structures and inter-union or association relationships in Ontario universities and uses both quantitative and qualitative data to illustrate how different structures influence internal debates about sessional contract academic faculty, bargaining priorities, and collective bargaining strategies. The authors conclude that bargaining unit structures have less of an impact than practitioners assume and that success at the bargaining table for sessional contract academic faculty is dependent on a broad range of factors rather than any particular structure.